Physical mechanisms of chromatin spatial organization. (22nd February 2021) - Chiariello, Andrea M.; Bianco, Simona; Esposito, Andrea; Fiorillo, Luca; Conte, Mattia; Irani, Ehsan; Musella, Francesco; Abraham, Alex; Prisco, Antonella; Nicodemi, Mario
Abstract : In higher eukaryotes, chromosomes have a complex three‐dimensional (3D) conformation in the cell nucleus serving vital functional purposes, yet their folding principles remain poorly understood at the single‐molecule level. Here, we summarize recent approaches from polymer physics to comprehend the physical mechanisms underlying chromatin architecture. In particular, we focus on two models that have been supported by recent, growing experimental evidence, the Loop Extrusion model and the Strings&Binders phase separation model. We discuss their key ingredients, how they compare to experimental data and some insight they provide on chromatin architecture and gene regulation. Progress in that research field are opening the possibility to predict how genomic mutations alter the network of contacts between genes and their regulators and how that is linked to genetic diseases, such as congenital disorders and cancer. Abstract : We review two main classes of polymer models employed to understand how the complex, functional 3D architecture of chromosomes is shaped within the cell nucleus. In the first class, represented by the SBS model, chromatin conformation is established via phase separation mechanisms by interactions between distal DNA sites. In the second class, represented by the LE model, contacts are determined by active motors that extrude DNA loops between distal anchoring sites.